FRI0619-HPR Joint Prostheses and Biologic Therapies in a Rheumatologic Clinic. (9th June 2015) - Lόpez Esteban, A.; Montoro, M.; Nieto González, J.C.; Flor, C.; González, C.M.; Janta, I.; Martínez-Barrio, J.; Hinojosa, M.; Bello, N.; Mata-Martinez, C.; Serrano, B.; Lόpez-Longo, J.; et al.
Abstract : Background: Biologic therapies (BT) have been changed considerably the treatment of autoimmune and autoinflammatory rheumatic diseases. However, patients with joint prostheses may present adverse effects due to these therapies. Objectives: To describe clinical features, treatment and complications of patients with joint prosthesis treated with BT. Methods: We included all patients treated in our BT Unit from January 2010 to December 2014. For each patient we analysed demographic, diagnosis, treatments, number of prostheses and complications. Results: Eight hundred patients were treated with TB in our TB Unit during the study period of which 77 (9.6%) patients needed joint prosthesis. The diagnosis of patients with joint prosthesis was as follows: 51 (66.2%) rheumatoid arthritis (RA), 16 (20.7%) ankylosing spondylitis (AS), 5 (6.5%) lupus erythematosus, 3 (3.9%) psoriatic arthritis and 2 (2.6%) juvenile idiopathic arthritis. We found 129 prostheses placed in the 77 patients, of which 56 (43.4%) were hip prostheses, 50 (38.7%) were knee prostheses, 5 (3.9%) were MCF prostheses, 4 (3.1%) were ankle prostheses, 3 (2.3%) were wrist prostheses, 2 (1.5%) were IF prostheses, 2 (1.5%) were elbow prostheses and 2 (1.5%) were shoulder prostheses. The mean age of prosthesis placing was 60 years (range 28-85) and the mean disease duration at the moment of prosthesis placing was 20 years. The most used BT were as follows: 28 (36.4%) infliximab, 20 (26%) rituximab, 16 (20.7%) tocilizumab, 9 (11.6%) abatacept and 4 (5.2%) etanercept. Thirty four (44.1%) patients had received more than one biological drug, 44 (57.1%) patients had concomitant synthetic disease-modifying anti-rheumatic drugs (sDMARDs) treatments and 41 (53.2%) patients had steroid treatment associated. We recorded 7 (5.4%) prosthetic infections in 7 (9.1%) patients of which 6 were diagnosed with RA and one with AS. From all infections, 2 occurred in prosthesis placed before the beginning of BT treatment and 5 occurred in prostheses placed during BT treatment. All patients with prosthesis infections were treated with concomitant sDMARDs and steroid treatment. Five patients needed prosthesis replacement for other reasons. Conclusions: Most frequent prostheses were hip and knee prostheses. The majority of prosthetic infection occurred in patients with prosthetic placement during the BT treatment. All patients with prosthesis infections received also sDMARS and steroid treatments. Disclosure of Interest: None declared